Paraprofessional library education in Canada: an environmental scan - James, Norene; Shamchuk, Lisa (My University, 2017)
This article represents a current environmental scan of 14 Canadian, English-speaking, paraprofessional library education diploma programs. The results were used to provide an overview of the development, current state, and possible future trends of paraprofessional library education in Canada. The patterns and relationships among the programs were identified, and the curriculum content of these traditionally skills-based programs was examined. It was discovered that the programs predominately focus on practical skill development, as evidenced by course titles and descriptions. Graduates may benefit from a greater proportion of courses that emphasize broader intellectual content in the curriculum, as recommended in recent studies on paraprofessional roles and industry changes.
Keywords: library education; paraprofessionals; Canada